2006
DOI: 10.1002/bit.21240
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced high copy number plasmid maintenance and heterologous protein production in an Escherichia coli biofilm

Abstract: Escherichia coli has been widely used for heterologous protein production (HPP). To determine whether a biofilm environment could benefit E. coli HPP using high copy number plasmids, we compared plasmid maintenance and HPP by E. coli ATCC 33456 containing plasmid pEGFP (a pUC family vector) cultivated in biofilms and in suspended culture. Cells were grown with or without antibiotic selective pressure in flow cells or chemostats for up to 6 days. In biofilms, antibiotic selective pressure increased the plasmid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
33
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 45 publications
(38 reference statements)
5
33
1
Order By: Relevance
“…1) (5). Few other references to increased plasmid copy number in biofilms were found, although enhanced maintenance of high-copy-number plasmids has been demonstrated (24). Davies and Geesey found that plasmid copy number was ϳ1.5 times higher in Pseudomonas aeruginosa biofilms than in planktonic cells (25) but, to our knowledge, this observation has not been further investigated.…”
Section: Discussionmentioning
confidence: 82%
“…1) (5). Few other references to increased plasmid copy number in biofilms were found, although enhanced maintenance of high-copy-number plasmids has been demonstrated (24). Davies and Geesey found that plasmid copy number was ϳ1.5 times higher in Pseudomonas aeruginosa biofilms than in planktonic cells (25) but, to our knowledge, this observation has not been further investigated.…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, although many efforts are being directed toward fighting biofilm formation or engineering strains with reduced biofilm formation abilities for biotechnological utilization (76), applications which exploit the biofilm formation abilities of harmless bacteria in a medical environment are presently being considered (19). A recent study demonstrating that, compared to planktonic cells, E. coli biofilms display enhanced high-copy-number-plasmid maintenance and heterologous protein production is also encouraging the use of biofilms in industrial applications (54). We showed in an in vitro experiment that a commensal MG1655 strain that constitutively expresses the Ag43 autotransporter adhesin (MG1655kmPcLflu) was more efficient than the isogenic MG1655⌬flu strain at competing for biofilm formation with a pathogenic enteroaggregative E. coli strain (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…11 The temporal single-cell measurements showed that the biofilm heterogeneity increases over time. O' Connell et al 10 studied the dynamics of fluorescence during biofilm development by flow cytometry and detected three populations of E. coli cells with differing levels of GFP expression in 24-h biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…11 The concentration gradients of the chemicals dissolved in the interstitial fluid within the biofilm matrix promote differences in bacterial enzymatic activities in different areas of the biofilms 12,13 and can create variation at the gene and protein levels. 10,[14][15][16] In this work, a protocol using fluorescence imaging is proposed for quantifying the dynamics of protein expression within a biofilm population at both bulk and singlecell levels. It should be noted that the entire protocol required only an epifluorescence…”
mentioning
confidence: 99%
See 1 more Smart Citation